Great enhancement of two photon absorption cross section value by intramolecular charge transfer in newly synthesized triphenylamine-BODIPY derivative. (September 2021) - Yildiz, Elif Akhuseyin; Sevinç, Gökhan; Tekin, Sezen; Karatay, Ahmet; Hayvalı, Mustafa; Elmali, Ayhan
Abstract: Novel borondipyrromethene (BODIPY) compound without a −8 ( meso ) substituent containing triphenylamine moieties via Suzuki-Miyaura coupling was designed and synthesized to enhance two photon absorption (TPA) property. The effect of π-expanded triphenylamine moieties and absence of meso substitution in BODIPY core on charge transfer dynamics as well as two photon absorption properties were investigated by utilizing ultrafast transient absorption spectroscopy measurements and open aperture (OA) Z-scan experiments in the environment of both in solution and host poly (methyl methacrylate) (PMMA) polymer film. The BODIPY compound with triphenylamine moieties has intramolecular charge transfer characteristics from electron donating moieties to BODIPY core due to its strong electron donating property and long conjugation length. The BODIPY compound with triphenylamine moieties demonstrates higher TPA cross section compared to reference compound based on the OA Z-scan experiments attributed to the strong coupling between the highest occupied molecular orbitals of BODIPY and 4-N, N-diphenylaminobiphenyl moieties. TPA cross section values were found to be 58 GM and 688 GM at 800 nm wavelength for reference BODIPY (BDP-1 ) and BODIPY-triphenylamine (BDP-2 ) compounds, respectively. BODIPY-triphenylamine compound has one of the greatest TPCS value among of the studied BODIPY compounds in the literature and may be a good candidate for photodynamic therapy and bio-imaging applications due to the free heavy atom nature. Graphical abstract: Image 1 Highlights: A novel BODIPY chromophore including triphenylamine moieties have been designed and synthesized to enhance TPCS value. TPCS values have been found to be 688 GM for BODIPY with triphenylamine moiety and 58 GM for reference BODIPY at 800 nm. Fs TA spectroscopy measurements proved intramolecular charge transfer from electron donating moieties to the BODIPY acceptor.